Social media marketing platforms use and effectiveness of marketing communication in the Tanzania ' s telecommunication industry: evidence from Vodacom Company - Mbura, Omari K. (University of Dar es Salaam Library Journal, 2021)
This paper shares the findings of a study that examined the role of social media marketing platforms in fostering the effectiveness of marketing communication in Tanzania ' s telecommunication industry. Specifically, it ascertains the extent to which people ' s awareness, attitude and skills facilitate the social media marketing platforms influence on the effectiveness of marketing communication. The study was conducted in the Tanzania ' s largest city of Dar es Salaam using Vodacom Company as a case study. Self-administered questionnaires were administered with 390 respondents and they yielded a response rate of 93.6% as 365 respondents returned the filled-out research tools. The resultant quantitative data were subjected to multiple regression analysis. The study established that, all the three independent variables had a positive influence but only two €”the users ' attitude and skills €”were strong predictors of effectiveness of marketing communication with a coefficient of less than 1%. These findings imply that, the organisation ' s management and policy efforts have to capitalise on enhanced people ' s skills and attitude towards social media platforms, as failure to do so might lead to organisational failure in realising the desired outcome from marketing efforts and hence, invite irrecoverable monetary cost. The research findings will be useful for both academics and managers who are interested in understanding and further committing to better use of the social media to enhance marketing communication practices.